Prophylactic Phenylephrine Infusions to Reduce Severe Spinal Anesthesia Hypotension During Cesarean Delivery in a Resource-Constrained Environment. (September 2017) - Bishop, David G.; Cairns, Carel; Grobbelaar, Mariette; Rodseth, Reitze N.
Abstract : Phenylephrine infusions are considered as standard management for obstetric spinal hypotension, but there remains reluctance to implement them in resource-limited contexts. This prospective, alternating intervention study of patients undergoing elective or urgent cesarean delivery under spinal anesthesia compared a vasopressor bolus strategy to fixed-rate, low-dose prophylactic phenylephrine infusion with supplemental boluses. The primary outcome was the incidence of severe hypotension (mean arterial pressure <70% baseline or systolic blood pressure <80 mm Hg). Fewer patients receiving prophylactic phenylephrine infusions had severe hypotension (47.4% [n = 120/253] vs 62.1% [n = 157/253], P = .001, estimated relative risk 0.84, 95% confidence interval, 0.69–1.02), with no significant difference in the rate of hypertension (15% [n = 39/253] vs 11% [n = 27/253], P = .11, estimated relative risk 1.39, confidence interval 0.87–2.20). Guidelines for resource-constrained settings should consider a fixed, low-dose phenylephrine infusion in combination with rescue vasopressor bolus therapy. Abstract : Published ahead of print February 24, 2017.